Quantum confinement in hydrogen bond of DNA and RNA - Santos, C. S. dos [UNESP]; Drigo Filho, E. [UNESP]; Ricotta, R. M. (Iop Publishing Ltd, 2015)
The hydrogen bond is a fundamental ingredient to stabilize the DNA and RNA macromolecules. The main contribution of this work is to describe quantitatively this interaction as a consequence of the quantum confinement of the hydrogen. The results for the free and confined system are compared with experimental data. The formalism to compute the energy gap of the vibration motion used to identify the spectrum lines is the Variational Method allied to Supersymmetric Quantum Mechanics.